2010
DOI: 10.1177/1477370810363375
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Inmates’ Anticipated Desistance

Abstract: This article addresses the importance of offenders’ perceived chances of anticipated desistance. The aim is to investigate to what extent anticipated desistance is associated with (objective) welfare deficiencies, perceived social status and personal agency as measured by the concept of perceived self-efficacy. Secondly, potential differences between men and women in the prediction of future chances of avoiding crime are investigated. Data derive from a survey of a nationwide representative sample of Norwegian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Moreover, our research confirms the utility of examining incarcerated women's outlook about their future. It suggests that examining whether and how incarcerated women maintain a positive outlook about their lives postrelease is an important avenue for better understanding the process involved in female's subjectively perceived prospects of postrelease success (see also Friestad & Hansen, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, our research confirms the utility of examining incarcerated women's outlook about their future. It suggests that examining whether and how incarcerated women maintain a positive outlook about their lives postrelease is an important avenue for better understanding the process involved in female's subjectively perceived prospects of postrelease success (see also Friestad & Hansen, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Zamble and Quinsey (1997) found that among their sample of 311 federal Canadian male inmates, most recidivists who returned to prison recalled having been ''fairly confident'' that they would succeed on the outside. And after surveying soon-to-be-released inmates in the state of Maryland, Visher and colleagues (2003) found that despite past parole violations and incarcerations, 78% of the 324 inmates (235 males and 89 females) sampled were optimistic about staying out of prison following their release (see also Friestad & Hansen, 2010). It is important to note, however, that Visher et al (2003) did not discuss gender differences and the studies mentioned above did not explore what influences prisoners' outlook regarding postrelease success.…”
Section: Optimism Inmates and Desistancementioning
confidence: 97%
“…Among others, the starting point is the question why some offenders continue to commit crime, while others stop, even when the same interventions are applied to them. This paradigm puts a special emphasis on the process of change, while emphasizing that this process involves continuous decision making at the individual level, and it is therefore necessary to take into account the offender's perception of his own problems and needs (Friestad and Skog Hansen, 2010;Shapland et al, 2012;Ward, 2012;Maloić, Mažar and Jandrić Nišević, 2013).…”
Section: Good Lives Model As An Alternative To the Model Of Risk-needmentioning
confidence: 99%
“…Criminal involvement during conditional release is related to involuntary readmission to a forensic hospital. In a study investigating factors associated with voluntary and involuntary readmissions to forensic hospitals, Marshall et al (19) found that treatment non-compliance and arrests predicted involuntary admissions. Furthermore, low numbers of community psychiatric admissions and a longer duration in the community prior to any psychiatric readmission were associated with desistance, i.e.…”
Section: Introductionmentioning
confidence: 99%